(untitled) (Tempo e Argumento, 2021)
This research examines the history of the doctrinal evolution of the United States Army in the period from 1959 to 2017. The article examines the dynamics of the changing conflict paradigm and its implications for the transformation of the U.S. Ground Force. Regarding methodological procedures, the research relied on the use of documents such as FM 3-24 Counterinsurgency (2006), the National Security Strategy (2017), and the Joint Operational Access Concept (2012). From a broad historical perspective and based on specialized literature, the scrutiny of the documents contributed to the understanding of the doctrinal evolution of the case under study, in the period from the Vietnam War to the War on Terror. In order to contribute to the history of the present time, we present how the processes assessed point to the contemporaneity of U.S. Army doctrine. The study was based on the theoretical arguments of Military History for the study of War, from multiple dimensional forms, based on cultural, technological, social, and also political fields